2006
DOI: 10.5194/angeo-24-1419-2006
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous radar and spaced receiver VHF scintillation observations of ESF irregularities

Abstract: Abstract. Simultaneous observations of equatorial spread F (ESF) irregularities made on 10 nights during MarchApril 1998 and 1999, using an 18-MHz radar at Trivandrum (77 • E, 8.5 • N, dip 0.5 • N) and two spaced receivers recording scintillations on a 251-MHz signal at Tirunelveli (77.8 • E, 8.7 • N, dip 0.4 • N), have been used to study the evolution of Equatorial Spread F (ESF) irregularities. Case studies have been carried out on the day-to-day variability in ESF structure and dynamics, as observed by 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…Another study by Patra et al (2005), who studied the spectral width of two radars using HF and VHF at equatorial stations, also reported that in the initial phase of the plasma bubbles the spectral width is found to be very high (300 m/s). The observations of fall in Ci index below 0.5 and high spectral width during early phase of plume observations by radar, presented by Tiwari et al (2006) and our observations are in agreement. In contrast to this, when bottomtype irregularities are seen in the radar map, the cross correlation index (Ci) does not decrease.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Another study by Patra et al (2005), who studied the spectral width of two radars using HF and VHF at equatorial stations, also reported that in the initial phase of the plasma bubbles the spectral width is found to be very high (300 m/s). The observations of fall in Ci index below 0.5 and high spectral width during early phase of plume observations by radar, presented by Tiwari et al (2006) and our observations are in agreement. In contrast to this, when bottomtype irregularities are seen in the radar map, the cross correlation index (Ci) does not decrease.…”
Section: Resultssupporting
confidence: 91%
“…Tiwari et al (2006) have attributed this to the large scale sinusoidal perturbations on the bottomside of the equatorial F region. Our observations presented here indicate that the bottomtype irregularities do not contain small scale irregularities of a few hundred meter scale size and also that spectral width observed during bottomtype irregularities is quite low, which is in agreement with the observations of Tiwari et al (2006). Niranjan et al (2003) have studied the post mid-night spread F over Waltair, India, using ionosonde observations.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Using this technique, Kakad et al [2007] have studied the fresh generation of irregularities around midnight hours and suppression of scintillations during pre‐midnight hours during magnetically active periods. From Tiwari et al [2006], one can notice that smaller the C I , higher the maximum height reached by the irregularity layer. Sripathi et al [2008] have studied the latitudinal extent of L‐band scintillations during different ESF events.…”
Section: Discussionmentioning
confidence: 92%
“…Eastward drifts at 300 km altitude estimated by Fukao et al . [] were found to be 140 m s −1 around 20 LT and 80 m s −1 around 24 LT. With regard to eastward drifts from Indian sector, there have been reports based on airglow imager and VHF scintillation observations [e.g., Sinha and Raizada , ; Tiwari et al ., ]. Using airglow imager observations from Sriharikota, a location ~100 km east of Gadanki, Sinha and Raizada [] estimated eastward drifts, which varied from 190 m s −1 at ~21 LT to 40 m s −1 at 01 LT. Tiwari et al .…”
Section: Resultsmentioning
confidence: 99%